Geographical variability in life‐history traits of a midslope dogfish: the brier shark Deania calcea. Issue 3 (September 2015) - Rochowski, B. E. A.; Walker, T. I.; Day, R. W.
<x xml:space="preserve">Abstract</x> Deania calcea (n = 420) were collected from the catch of deep‐water trawlers in the southern and eastern scalefish and shark fishery in southern Australia during the years 2008–2011. The total length (LT) range varied between sexes, females being larger (n = 264; 280–1530 mm) than males (n = 156; 310–921 mm). The reproductive cycle in this population is non‐continuous and asynchronous. The estimated LT at which 50% of males are mature is 807 mm and is 914 mm for females. Populations of D. calcea in higher latitudes appear to mature at a larger size than conspecifics in lower latitudes, in both the northern and southern hemispheres. Litters ranged from three to 10 embryos with a 1:1 sex ratio, but litter size does not increase with maternal LT. Deania calcea shows geographical variability in its biological parameters and gathering information on life‐history traits of populations is vital to understand the trade‐offs made by this species in response to environmental conditions and to predict intraspecific spatial differences. Such information is a basis for specific spatial management to protect populations from excessive fishing.